Circulating Endothelial Cells in Patients with Heart Failure and Left Ventricular Dysfunction - Martínez-Sales, Vicenta (IOS Press, 2011)
Introduction and Aims: Acute and chronic heart failure may manifest different degrees of endothelial damage and angiogenesis. Circulating endothelial cells (CEC) have been identified as marker of vascular damage. The aim of our study was to evaluate the evolution of the CEC at different stages of patients with heart failure. We also investigated a potential correlation between CEC and markers of vascular damage and angiogenesis. Methods: We studied 32 heart failure patients at hospital admission (acute phase) and at revision after 3 months (stable phase) and 32 controls. Circulating markers of endothelial damage (CEC; von Willebrand factor, vWF and soluble E-selectin, sEsel) and angiogenesis (vascular endothelial growth factor, VEGF and thrombospondin-1) were quantified. Results: Levels of CEC, vWF, sEsel and VEGF are significantly higher in heart failure patients than in controls. Levels of CEC (36.9 ± 15.3 vs. 21.5 ± 10.0 cells/ml; p < 0.001), vWF (325 ± 101 vs. 231 ± 82%; p < 0.001) and VEGF (26.3 ± 15.2 vs. 21.9 ± 11.9 ng/ml; p < 0.001) are significantly higher in the acute phase than in the stable phase of heart failure. CEC levels correlate with vWF and VEGF. Results show than 100% of patients in acute phase and 37.5% in stable phase have levels of CEC higher than the 99th percentile of the distribution of controls (16 cells/ml). Therefore, increases in CEC represent a relative risk of 9.5 for heart failure patients suffering from acute phase. Conclusions: CEC, in addition to being elevated in heart failure, correlate with vWF levels, providing further support for CEC as markers of endothelial damage. Levels of CEC are associated with the acute phase of heart failure and could be used as a marker of the worsening in heart failure.